2020
DOI: 10.1049/iet-stg.2019.0091
|View full text |Cite
|
Sign up to set email alerts
|

AI in arcing‐HIF detection: a brief review

Abstract: In the past few decades, the arcing-high-impedance fault (arcing-HIF) detection problems have become an important issue in the effectively grounded distribution network. Many solutions have been proposed to address this problem. The most attractive way is artificial intelligence (AI) method. The paper gives a comprehensive review of arcing-HIF detection in distribution network-based AI. First, characteristics and models of arcing-HIF are analysed, the arcing-HIF database construction method is also explained; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Other methods utilize various signal processing-based techniques for HIF detection. These techniques are classified based on domain analysis into the time, frequency, time scale, and time-frequency domains [6,10]. Time-domain methods that employ behavior analysis, magnitudes, and sequences as detecting factors have been presented as an alternative to conventional mechanical procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods utilize various signal processing-based techniques for HIF detection. These techniques are classified based on domain analysis into the time, frequency, time scale, and time-frequency domains [6,10]. Time-domain methods that employ behavior analysis, magnitudes, and sequences as detecting factors have been presented as an alternative to conventional mechanical procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This fault, usually accompanied by an electric arc, causes massive fires, leading to costly damages and potential loss of life. Despite the severity of HIFs, diagnosing these faults remains challenging due to their peculiar characteristics and low current draw, typically less than 75A [5,6]. According to Electrical safety reports, only 17.5% of HIFs were detected and eliminated by traditional protection techniques such as over-current relays.…”
Section: Introductionmentioning
confidence: 99%
“…In 1949, the Power Systems Relaying Committee Working Group concluded that it was impossible at that time to develop techniques for detecting HIF [9]. However, especially in the last four decades, many researchers have been working to develop techniques that can detect, classify, and/or locate this type of fault [3], [6], [10], [11]. Despite the several studies presented in the literature, this research problem still lacks a definitive solution that presents high reliability and security in terms of detection and differentiation between the occurrence of HIF and other events common to distribution systems, such as switching loads or capacitors bank [6], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a comprehensive understanding of such faults is a necessity for many engineers in order to innovate practical solutions. The authors of [1,2] introduced an HIF detection-oriented review. Their research defined the HIF problem as a pattern classification task that can be encountered using neural network classifiers trained via features extracted from measurements (i.e., current, voltage, and magnetic field intensity).…”
Section: Introductionmentioning
confidence: 99%
“…. The evaluation criteria of such papers can depend on the following[2,31]:1. Accuracy is used to measure the performance of proposed techniques against the expected results.…”
mentioning
confidence: 99%